Characterization of Three Pleiotropic Drug Resistance Transporter Genes and Their Participation in the Azole Resistance of Mucor circinelloides - Nagy, Gábor; Kiss, Sándor; Varghese, Rakesh; Bauer, Kitti; Szebenyi, Csilla; Kocsubé, Sándor; Homa, Mónika; Bodai, László; Zsindely, Nóra; Nagy, Gábor; Vágvölgyi, Csaba; Papp, Tamás (Frontiers in Cellular and Infection Microbiology, 2021)
Mucormycosis is a life-threatening opportunistic infection caused by certain members of the fungal order Mucorales. This infection is associated with high mortality rate, which can reach nearly 100% depending on the underlying condition of the patient. Treatment of mucormycosis is challenging because these fungi are intrinsically resistant to most of the routinely used antifungal agents, such as most of the azoles. One possible mechanism of azole resistance is the drug efflux catalyzed by members of the ATP binding cassette (ABC) transporter superfamily. The pleiotropic drug resistance (PDR) transporter subfamily of ABC transporters is the most closely associated to drug resistance. The genome of Mucor circinelloides encodes eight putative PDR-type transporters. In this study, transcription of the eight pdr genes has been analyzed after azole treatment. Only the pdr1 showed increased transcript level in response to all tested azoles. Deletion of this gene caused increased susceptibility to posaconazole, ravuconazole and isavuconazole and altered growth ability of the mutant. In the pdr1 deletion mutant, transcript level of pdr2 and pdr6 significantly increased. Deletion of pdr2 and pdr6 was also done to create single and double knock out mutants for the three genes. After deletion of pdr2 and pdr6, growth ability of the mutant strains decreased, while deletion of pdr2 resulted in increased sensitivity against posaconazole, ravuconazole and isavuconazole. Our result suggests that the regulation of the eight pdr genes is interconnected and pdr1 and pdr2 participates in the resistance of the fungus to posaconazole, ravuconazole and isavuconazole.